2021
DOI: 10.1186/s12889-021-11624-9
|View full text |Cite
|
Sign up to set email alerts
|

Occupational class differences in outcomes after ischemic stroke: a prospective observational study

Abstract: Background Occupational class is an integral part of socioeconomic status. The studies focused on the occupational difference in ischemic stroke outcome in a Chinese population are limited. We aimed to investigate the associations between occupational class and the prognosis of patients with ischemic stroke in China. Methods We included 1484 ischemic stroke participants (mean age: 63.42 ± 11.26 years) from the prospective cohort study: Infectious F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…[ 4 , 5 ]. According to epidemiological statistics, the prognosis of ischemic stroke is not ideal, with 27% of vascular events occurring within 1 year and 45% within 5 years [ 6 ]. Currently, there is no effective treatment for ischemic stroke, and the conventional treatment schemes include anticoagulation, neuroprotective drugs, and platelet anticoagulation drugs [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ]. According to epidemiological statistics, the prognosis of ischemic stroke is not ideal, with 27% of vascular events occurring within 1 year and 45% within 5 years [ 6 ]. Currently, there is no effective treatment for ischemic stroke, and the conventional treatment schemes include anticoagulation, neuroprotective drugs, and platelet anticoagulation drugs [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 23 studies (22-24, 26, 28, 29, 32-35, 48) enrolled patients with first-episode ischemic stroke, and five studies (25,27,30,31,44) selected patients with ischemic and hemorrhagic stroke but reported separately. In addition, 16 studies (23, 25, 27, 28, 30, 32, 35-38, 41, 42, 44, 49) defined cognitive reserve indicators as socioeconomic status, eight studies (22,24,29,31,40,43,45,47) used education attainment, two studies (26, 39) measured premorbid IQ, and one study each estimated bilingualism (34) and occupation (48).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Based on the QUIPS tool, no studies were excluded. In short, five (27,29,31,32,34) out of 28 studies were rated as having a high risk of bias, eight (22,24,26,39,(45)(46)(47)(48) as moderate, and 15 (23, 25, 28, 30, 33, 35-38, 40-44, 49) as low. Overall, the risk of six domains was judged to vary from low to high-risk bias, respectively, in "study participation" (low risk: 60.71%, moderate risk: 32.13%, and high risk: 7.14%), "study attrition" (low risk: 39.29%, moderate risk: 53.57%, and high risk: 7.14%), "prognosis factor measurement" (low risk: 71.43%, moderate risk: 25.00%, and high risk: 3.57%), "outcome measurement" (low risk: 92.86% and moderate risk: 7.14%), "study confounding" (low risk: 71.43%, moderate risk: 25.00%, and high risk: 3.57%), and "statistical analysis and reporting" (low risk: 46.43% and moderate risk: 53.57%) (Figure 2).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A model included the number of expected deaths as an offset term to adjust for the population size of each municipality. Moreover, in terms of municipality-level socioeconomic status variables, this study adopted; the ratio of people who completed college and university studies (%), the proportion of workers in primary industries (%), such as agriculture and fishing, the proportion of workers in secondary industries (%), such as manufacturing and construction, and the proportion of workers in tertiary industries (%), mainly services [14][15][16][17]. However, these socioeconomic values were impact of socioeconomic factors on stroke is a global challenge, and improving access to healthcare may reduce disparities in outcomes.…”
Section: Response and Explanatory Variablesmentioning
confidence: 99%